Design, construction and implementation of an auto mated system integration flow, pressure and temperature modules for CEMA - Poma Deza, Jorge (2012)
The article presents an alternative for manufacturing and process industry, aims to integrate flow, pressure and temperature modules automated for Centro de Manufactura Avanzada (CEMA-UNMSM) through Microcontroller, responding to the need of the business sector, to improve their productivity by using economic technology to increase product quality and reduce manufacturing costs. The results achieved in the research is the integration of process control systems for CEMA, which brings in conclusion the feasibility of functional devices reduced installation space, versatile and easy process operation using software.